Design and experiment on intelligent fuzzy monitoring system for corn planters - Ruicheng, Du; Bingcai, Gong; Ningning, Liu; Chenchen, Wang; Zidong, Yang; Mingjian, Ma (International Journal of Agricultural and Biological Engineering, 2013)
When sowing summer corn without tillage, it is necessary to ensure that the furrow opener is free from straw congestion and that the spacing of the sowing can be adjusted according to the breeds of corn and the preset seeding rate per acre. On the basis of the structural features of newly developed no-tillage corn fertilizers, an intelligent fuzzy monitoring system for corn planters was developed in this study. The system facilitates automatic control of the spacing adjustment and the status monitor for the fertilizer tank, seed tank, and seeding orifice. According to the preset number of rows, line spacing, number of plants per acre, and seed germination rate, the control rate can be calculated through designing in surveillance software. The control rate is output to the fuzzy controller through the digital output module of the CAN bus. Fuzzy control is applied to the DC motor for stepless adjustment of the spacing. A system for video surveillance of the working status of a planter is developed for displaying a real-time video image of the planter operation and achieving an anti-congestion status monitoring of a no-tillage planting operation in a dusty environment. Through field trials, the detection accuracy was 91.4%. The seed-clogging fault-alarm accuracy was 96.0%. The entire system remained stable and reliable.